Destination Brand Satisfaction in Nature-Based Tourism: Image and Experience as Primary Drivers - Sembiring, Beby Karina Fawzeea; Rini, Endang Sulistya; Nasution, Muhammad Dharma Tuah Putra (International Review of Management and Marketing, 2025)
This study examines how destination branding elements influence tourist satisfaction in nature-based destinations, with implications for sustainable tourism management strategies. A survey of 350 domestic tourists visiting Lake Toba, Indonesia examined relationships between destination image, service environment, social interactions, tourist experiences and satisfaction. Structural equation modelling tested the conceptual framework. Destination brand image strongly influences tourist experiences and satisfaction, whilst service quality and social interactions show limited impact in this nature- based context. Tourist experiences serve as the primary driver of satisfaction. The results provide empirical evidence for contextual differences in destination satisfaction mechanisms. Destination managers in nature-based contexts should prioritise authentic branding and experiential design over traditional service improvements, whilst recognising contextual variations in tourist expectations. The research provides empirical evidence for boundary conditions of service-dominant logic in destination management, demonstrating that satisfaction mechanisms vary across destination types and extending destination branding theory through contextual validation.